2016
DOI: 10.5812/ijhrba.36313
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Personality Pattern Behaviors in Risk Behaviors of High School Students

Abstract: Background: There are many risky behaviors that threat adolescents and must receive specific attention. Research has shown that personality pattern behaviors have a significant relationship with risky behaviors. Objectives: The objective of this study was to clarify the role of personality pattern behaviors in risky behaviors of high school students in Chabahar city. Patients and Methods: Three hundred high school students from Chabahar city were selected at random for this study and filled Type A and B patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In Australia, individuals experiencing psychological distress possess an increasing tendency to adopt risky sexual behaviours (Ganczak et al, 2017;Nguyen et al, 2017), while perceived self-esteem among adolescents is found to be a significant correlate with their practice of risky sexual behaviour. Furthermore, one study among Mexican adolescents has found that self -efficacy is linkable sexual risk behaviour of young people while this scenario also plays out in Iran where it was found that personality pattern is a significant predictor of risky sexual behaviours (Palacios, 2018;Samadypoor & Kord Tamini, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In Australia, individuals experiencing psychological distress possess an increasing tendency to adopt risky sexual behaviours (Ganczak et al, 2017;Nguyen et al, 2017), while perceived self-esteem among adolescents is found to be a significant correlate with their practice of risky sexual behaviour. Furthermore, one study among Mexican adolescents has found that self -efficacy is linkable sexual risk behaviour of young people while this scenario also plays out in Iran where it was found that personality pattern is a significant predictor of risky sexual behaviours (Palacios, 2018;Samadypoor & Kord Tamini, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…When the triangular relationship of these behaviors is accepted; it could be accepted that all of them have a common origin. Stress may contribute as the main source of all of these three themes ( 57 ). In other words, high-risk sexual behavior, addiction, and aggression are all one social problem with different manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…The self-centeredness of adolescence makes them feel unique and take dangerous actions based on this personal fable that they are invulnerable. The occurrence and persistence of these behaviors cause serious physical, psychological, and sociological consequences and reduce their quality of life now and in the future (2)(3)(4)(5). This has caused serious concern for families and the community (4).…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence and persistence of these behaviors cause serious physical, psychological, and sociological consequences and reduce their quality of life now and in the future (2)(3)(4)(5). This has caused serious concern for families and the community (4). By presenting the problem behavior syndrome, Jessor identified risky behaviors, including smoking, drug use, alcohol, dangerous driving, and early sexual behaviors (6).…”
Section: Introductionmentioning
confidence: 99%